Patenting Public-Funded Research for Technology Transfer: A Conceptual-Empirical Synthesis of US Evidence and Lessons for India - Amit Shovon Ray; Sabyasachi Saha (Indian Council for Research on International Economic Relations (ICRIER), 2010)
The question of protecting intellectual property rights by academic inventors was never seriously contemplated until the introduction of the Bayh-Dole Act in 1980 in the US. The Act allowed universities to retain patent rights over inventions arising out of federally-funded research and to license those patents exclusively or nonexclusively at their discretion. This particular legislation was a response to the growing oncern over the fact that federally funded inventions in the US were not reaching the market place. In this paper, we present a critical review of the US experience after the Bayh-Dole Act and argue that the evidence is far from being unambiguous. We discuss the debate surrounding the Act - the extent to which it was successful in achieving its objectives, the unintended consequences, if any, and more generally, the effectiveness of IPR as a vehicle of technology transfer from universities. We also discuss the limited evidence on Bayh-Dole type legislations introduced in other countries. A new legislation, along the lines of the US Bayh-Dole Act - The Protection and Utilisation of Public Funded IP Bill, 2008 - is presently before the Indian parliament. The paper presents an Indian perspective against the backdrop of the US experience in an attempt to draw concrete lessons for India.
Keywords: O31; O34; O38; I23; I28; 330; Bayh-Dole Act; public-funded research; universities; patents; India; Universitäre Forschung; Patentrecht; Forschungskooperation; Technologiepolitik; USA; Vergleich; Indien